Efektivitas Program Pemberian Makanan Tambahan (PMT) terhadap Partisipasi Masyarakat di Desa Maddenra Kacamatan Kulo Kabupaten Sidenreng Rappang - Aulia Rahman; Andi Uceng; Lukman Lukman (Yayasan Literasi Sains Indonesia, 2025)
This study aims to determine the effectiveness of the Supplementary Feeding Program (PMT) on community participation in Maddenra Village, Kulo District, Sidenreng Rappang Regency. Nutritional problems such as stunting and chronic energy deficiency are still challenges, and PMT is one of the government's interventions in overcoming them. The research method used is a quantitative approach with descriptive analytical techniques. The sample consisted of 30 respondents consisting of pregnant women and toddlers. Data were collected through observation, questionnaires, and literature studies. The results of the study showed that Supplementary Feeding (PMT) in Maddenra Village was considered